Determinan Penanaman Modal Asing di Indonesia Tahun 2018-2023 - Rachel Pradita, Elviandra; Usman, Moneyzar; Ananta, Prayudha (CV. ITTC INDONESIA, 2024)
Foreign investment is one of the most important drivers of economic growth for Indonesia. In the midst of the challenging global economic dynamics, including the impact of the pandemic and geopolitical tensions, Indonesia is still showing its attractiveness to foreign investors. This study aims to determine the effect of GRDP Per capita, Provincial Minimum Wage, Tax Ratio, Inflation and Covid-19 Pandemic on Foreign Investment in Indonesia in 2018-2023. The data used in this study is quantitative panel data with a sample population of 34 provinces in Indonesia. The research method uses multiple linear regression analysis with the fixed effect model (FEM) as the best model. The regression results show that GRDP per capita and tax ratio have a significant positive effect, provincial minimum wage has an insignificant negative effect, while inflation and Covid-19 dummy have no significant effect on foreign investment in Indonesia in 2018-2023. This study indicates that the level of people's purchasing power accompanied by qualified infrastructure improvements can attract foreign investment, but it must still be matched by pro-investment government policies for mutual benefits.